Penerapan Alat Uji Attrakdiff pada Perancangan Sistem Informasi Managemen Tugas Berbasis Web (Studi Kasus di Yayasan Lembaga SABDA) - Kristono Kristono; Abraham Aji; BRM. Suryo Triono; Herjuno Pramudito (Sekolah Tinggi Manajemen Informatika dan Komputer AUB - Indonesia, 2026)
The ITS (Information Technology Service) team serves as the technology division of the SABDA Foundation, an organization dedicated to developing digital platforms and applications that support Christian learning. Each morning, the team holds a brief scrumb meeting to determine the IT projects to be handled that day, with HRD recording all decisions using a laptop. Because task prioritization and assignment are still managed manually, the workflow often becomes difficult to track especially as the number of projects grows and staff members need clear information about urgent tasks, postponed work, and assignments approaching or exceeding their deadlines. To address this issue, this study develops a web‑based task management information system built with PHP, MySQL, and Bootstrap 5.3. The system includes login access for both admin and users, user management features for the admin, and task categorization such as completed tasks, overdue tasks, tasks within deadline, and postponed tasks. Users can view their assigned tasks, update task status, and receive notifications related to their responsibilities. With this system, ITS staff can monitor their workload more independently, while admins gain a clearer overview of project progress. The system has been successfully implemented with all planned features and is ready to enhance coordination and performance within the ITS team at the SABDA Foundation.